(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This study explores the goods of an automated corrective feedback- grounded peer assessment approach on learners’ pronunciation development, provocation, and tone- regulated literacy in a foreign language environment. predicated in constructivist and pupil- centred perspectives, aquasi-experimental design was conducted with undergraduate scholars learning French, who were assigned to experimental and control groups. While the experimental group engaged in AI- supported feedback integrated with structured peer assessment conditioning, the control group entered conventional schoolteacher- led feedback. Data were collected through pre- and post-tests, questionnaires, and interviews to capture both performance issues and learner comprehensions. The findings suggest that the integration of automated feedback with peer assessment contributes to conspicuous advancements in pronunciation performance and supports the development of natural provocation and tone-nonsupervisory chops. Although foreign provocation remained largely innocent, scholars in the experimental group displayed advanced situations of engagement, autonomy, and reflective literacy practices. Qualitative results farther indicate that learners appreciated the proximity, clarity, and substantiated nature of feedback, as well as the occasion to laboriously share in cooperative evaluation processes.